Tratamiento e Interpretación de la Educación Física durante el enfoque legislativo Franquista (1939-1970) (Treatment and Interpretation of Physical Education during the Francoism legislative approach (1939-1970)) - Ruiz-Montero, Pedro Jesús; Chiva-Bartoll, Oscar; Colomer-Rubio, Juan Carlos; Leiva-Olivencia, Juan (Retos, 2020)
El estudio describe el tratamiento de la Educación Física bajo las leyes franquistas aprobadas tras 1939, para concluir el importante efecto de la orientación política de esta disciplina escolar hasta su progresiva modernización en los 70s. El trabajo parte de los estudios realizados sobre historia de la Educación Física en España durante el franquismo (1936-1975) que han versado sobre dos ejes: el ideal moralizador de la Educación Física acorde con el contexto político-social del momento y los estudios que han analizado los hábitos de práctica física y gimnástica de organizaciones políticas dependientes al régimen, como “Frente de Juventudes” o la “Sección Femenina”. Como conclusión se aportan aspectos relevantes sobre la interpretación de la Educación Física desde las diferentes referencias legislativas y otros documentos durante la dictadura que podrían ayudar a entender diversas perspectivas de esta área. Abstract. The present study describes the treatment and interpretation of Physical Education under Franco's laws passed after 1939, so to discuss the important effect of the political orientation of this school subject until its progressive modernization in the 70's. History of Physical Education in Spain during the dictatorship of Franco (1936-1975) has dealt with two basic axes: the moralizing ideal of Physical Education according to the political-social context of the moment, and the studies that have analysed the habits of Physical and gymnastic practice of political organizations subject to the regime, such as "Frente de Juventudes" or "Sección Femenina". In conclusion, relevant aspects are presented on the interpretation of Physical Education from different legislative references and other documents during the dictatorship that could help understand diverse perspectives of this area, according to the examined Education Law.